The threat from without - Saressalo, Lassi (The Donner Institute, 2014)
Of greatest importance in ethnic folklore are the recognised and unrecognised elements that are used when founding identity on tradition. For the aim of ethnic identification is to note and know the cultural features that connect me with people like me and separate me from people who are not like me. Every group and each of its members thus needs an opponent, a contact partner in order to identify itself. What about the Lapps? The ethnocentric values of ethnic folklore provide a model for this generalising comparison. 'They' are a potential danger, are unknown, strange, a threat from beyond the fells. They are sufficiently common for the group's ethnic feeling. It is here that we find tradition, folk tales, describing the community's traditional enemies, describing the threat from without, engendering preconceived ideas, conflicts and even war. The Lapps have never had an empire, they have never conquered others' territory, they have never engaged in systematic warfare against other peoples. For this reason Lapp tradition lacks an offensive ethnic folklore proper with emphasis on aggression, power, violence, heroism and an acceptance of the ideology of subordinating others. On the contrary,Lapp folklore is familiar with a tradition in which strangers are always threatening the Lapps' existence, plundering their territories, burning and destroying. The Lapp has always had to fight against alien powers, to give in or to outwit the great and powerful enemy. In the Lapp tradition the staalo represents an outside threat that cannot be directly concretised. If foes are regarded as concrete enemies that may be defeated in physical combat or that can be made to look ridiculous, a staalo is more mythical, more supranormal, more vague. One basic feature of the staalo tradition is that it only appears as one party to a conflict. The stories about the Lapp who succeeds in driving away a staalo threatening the community, to outwit the stupid giant or to kill him with his own weapon come close to the myth of the beginning of ...